Insights into the development of microbial fuel cells for generating biohydrogen, bioelectricity, and treating wastewater - Ahmed S.F.; Mofijur M.; Islam N.; Parisa T.A.; Rafa N.; Bokhari A.; Kleme J.J.; Indra Mahlia T.M. (Elsevier Ltd, 2023)
Electric power generation; Electrodes; Electrophysiology; Hybrid materials; Hydrogen; Membranes; Microbial fuel cells; Regenerative fuel cells; Bio-electrochemical systems; Bio-hydrogen; Conventional fuel; Design and application; Fuel cell application; Fuel cell designs; Fuel energy; Lignocellulosic biomass; Proton-exchange; Review papers; Wastewater treatment; biofuel; cellulose; electricity; electrode; fuel cell; hydrogen; wastewater treatment